FINANCIAL FEASIBILITY AND RISK ANALYSIS OF HIGH-VALUE HORTICULTURAL FARMING: A COMPARATIVE REVIEW BETWEEN DEVELOPED AND DEVELOPING COUNTRIES - Roeury, Yon; Sitompul, Thomson (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2026)
Horticultural farming, particularly high-value vegetable production such as chili, tomatoes, and leafy vegetables, plays a strategic role in increasing farm income and supporting rural economic development in both developed and developing countries. This study aims to analyze the financial feasibility and risk factors associated with horticultural farming through a comprehensive literature review approach. Secondary data were systematically collected from peer-reviewed journals, institutional reports, and international publications focusing on financial indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Benefit–Cost Ratio (BCR), and Payback Period (PP), as well as sensitivity and risk analyses. The findings reveal that horticultural farming is generally financially feasible across different country contexts. In developed countries, modern systems such as greenhouse and hydroponic production demonstrate strong profitability despite high initial capital requirements, supported by technological efficiency and stable market integration. In developing countries, smallholder horticulture generates significantly higher returns compared to staple crops; however, financial viability is more vulnerable to price volatility, input cost fluctuations, limited infrastructure, and market access constraints. Risk management strategies—including contract farming, cooperative marketing, technological adoption, institutional support—are critical in maintaining long-term financial sustainability. In Indonesia, particularly in chili farming, the evidence suggests that horticultural investment can be highly profitable but requires comprehensive financial planning and risk mitigation measures to withstand market and production uncertainties. This review highlights the importance of integrating financial feasibility analysis with risk assessment to enhance farm resilience, improve profitability, and support sustainable horticultural development.